Pengembangan Social Entrepreneurship Melalui Pemberdayaan Kelompok Masyarakat Sebagai Upaya Peningkatan Kesejahteraan Ekonomi Umat di Kabupaten Banjarnegara - Sarno; Muhamad Solekan; Dwi Putriana Nuramanah Kinding (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2024)
The Fatayat Nahdlatul Ulama (NU) Branch of Banjarnegara is one of the Islamic-based community organizations that uphold the principles of Ahlul Sunnah Wal Jama'ah in Banjarnegara Regency. One of the efforts to foster the spirit of entrepreneurship, particularly social entrepreneurship, is by developing productive economic-based businesses. This business development is realized through the establishment of cooperative enterprises. The goal achieved is to assist the community groups of Fatayat NU Branch of Banjarnegara in enhancing their knowledge of social entrepreneurship and cooperative business development to improve the welfare of the people. This community service activity is carried out using the Participatory Rural Appraisal (PRA) method through educational activities, mediation, and community assistance approaches. The target outcomes of the activity include an 81.8% increase in knowledge among management and members regarding social entrepreneurship, a 59.1% increase in entrepreneurship knowledge and experience, and a 100% improvement in cooperative business development. The community service activity can be considered successful and has achieved the set targets.